Programmes of Industrial Development 1961-66 - Planning Commission (Planning Commission, 1961)
Following the reports on the two five-year plans of India, the Planning Commission brought out in December, 1952 and in July, 1956 separate volumes on the Programmes of Industrial Development. In the volume published in 1956, the progress recorded by selected industries in the preceding quinquennium as compared to forecasts made earlier and the targets and programmes under the Second Five Year Plan, which had been outlined in a nutshell in the Chapter on Industries of the main report, were elaborated in considerable detail. In the present volume some new industries have been dealt with for the first time, and the same function has been fulfilled as in the past by bringing together statistical data relating to 75 organised industries together with programmes for their expansion during the period of the Third Five Year Plan.
Government of India Planning Commission
Government of India Planning Commission